2014
DOI: 10.5539/ass.v10n17p265
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance in Processing English Non-restrictive Relative Clauses in Thai EFL Learners’ Interlanguage

Abstract: This paper examined the acquisition of English non-restrictive relative clauses (NRCs) by L1 Thai learners, focusing on avoidance strategies applied in the learners' interlanguage. The theoretical frameworks of the Noun Phrase Accessibility Hierarchy (NPAH) and the Perceptual Difficulty Hypothesis (PDH) were the main hypotheses predicting avoidance behavior employed by the learners. The research participants were 80 Thai EFL high school students of high and low proficiency levels. The data were elicited throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Abdolmanafi & Rahmani, 2012;Rattanasak & Phoocharoensil, 2014;Gao, 2014;Alotaibi, 2016). Furthermore, these subsequent research studies have shed light on solutions to problems encountered by EFL learners when studying English RCs.…”
Section: International Journal Of Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdolmanafi & Rahmani, 2012;Rattanasak & Phoocharoensil, 2014;Gao, 2014;Alotaibi, 2016). Furthermore, these subsequent research studies have shed light on solutions to problems encountered by EFL learners when studying English RCs.…”
Section: International Journal Of Educationmentioning
confidence: 99%
“…The study was conducted to measure the extent to which the participants avoided using relative clause constructions. Rattanasak and Phoocharoensil (2014) then analyzed the results based on the predictions outlined by the NPAH and Kuno's Perceptual Difficulty Hypothesis (PDH) (1974), which is based on the idea that the fickleness of the human memory system makes centrally embedded relative clauses more difficult to process. The results show a high percentage of avoidance, particularly, when dealing with the 'object of adposition' and 'genitive' clauses.…”
Section: International Journal Of Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Later researchers working on L2 English avoidance studies found avoidance of L2 structures by learners from several L1 backgrounds, e.g. avoidance of English phrasal verbs by L1 Hebrew, Swedish, Dutch, and Thai learners (Dagut & Laufer, 1985;Hulstijn & Marchena, 1989;Kosolsombat & Pongpairoj, 2017;Laufer & Eliasson, 1993); avoidance of English relative clauses by L1 Thai learners (Rattanasak & Phoocharoensil, 2014;Thiamtawan & Pongpairoj, 2013); avoidance of inversions (Thiamtawan & Pongpairoj, 2019); and avoidance of the English passive construction by L1 Arabic, Spanish, Portuguese, Hebrew, and Thai learners (Chotiros & Pongpairoj, 2012;Kleinmann, 1977;Seliger, 1989). In the context related to L1 Chinese learners, researchers also examined some English structures in their avoidance studies, e.g.…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%